BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Indian Plant Viruses and Mycoplasma. Authors : V.K. Gupta and M.K. Behl Kalyani Publishers, Ludhiana, New Delhi, NOIDA (UP),Hyderabad, Madras, Calcutta, Cuttack, 1993,232Â pp, price Rs. 350.